Advances in epigenetic modifications of autophagic process in pulmonary hypertension - Mao, Min; Song, Shasha; Li, Xin; Lu, Jiayao; Li, Jie; Zhao, Weifang; Liu, Hanmin; Liu, Jingxin; Zeng, Bin (Frontiers in Immunology, 2023)
Pulmonary hypertension is characterized by pulmonary arterial remodeling that results in increased pulmonary vascular resistance, right ventricular failure, and premature death. It is a threat to public health globally. Autophagy, as a highly conserved self-digestion process, plays crucial roles with autophagy-related (ATG) proteins in various diseases. The components of autophagy in the cytoplasm have been studied for decades and multiple studies provided evidences shown the importance of autophagic dysfunction in pulmonary hypertension. The status of autophagy plays a dynamic suppressive or promotive role in different contexts and stages of pulmonary hypertension development. Although the components of autophagy have been well studied, the molecular basis for the epigenetic regulation of autophagy is less understood and has drawn increasing attention in recent years. Epigenetic mechanisms include histone modifications, chromatin modifications, DNA methylation, RNA alternative splicing and non-coding RNAs, which control gene activity and the development of an organism. In this review, current research progress on epigenetic modifications in autophagic process was summarized, which have the potential to be a crucial and powerful therapeutic target against autophagic process in pulmonary hypertension development.